Analisis Faktor yang Mempengaruhi Kualitas Hidup pada Pasien Penderita Kanker Payudara di Rumah Sakit - Priyadi, Akhmad; Japar Sodik, Jajang; Maulana Sobandi, Mamay; Saidah Mutmainah, Siti; Sabarudin, Cecep; Aqila Fadia, Andira (Public Health and Safety International Journal, 2025)
Breast cancer ranks top of all types of cancer experienced by women with an average prevalence of 56.5 per 100,000 female populations in the world. In Indonesia, less than 68,858 cases (16.6%) of a total of 396,914 cases were recorded and more than 22,000 cases ended in death. (Sung et al., 2021). The life of a patient diagnosed with breast cancer will experience many changes in their physical and psychological condition, which will then affect the quality of life of the patient and will be a long-term problem if not treated. Individuals with good quality of life will have physical and mental health, which will enable them to live socially in society according to their role. T The research was conducted quantitatively using cross sectional designs. The sample was used by 75 respondents who met the inclusion criteria of the population at the Hospital. The dependent variable is the quality of life of breast cancer patients, while the independent variables are age, marital status, lifestyle, body mass index, and stage of cancer. Data is collected using EORTC QLQ-C30 questionnaire, which are then analyzed by validating SPSS with an ordinal regression test. The results of the study showed that there was no influence between age (p=0.891), lifestyle (p =0.247), body mass index (p_0.294), and stage of cancer (p−0.268). Whereas for marital status(p=0,000) there was influence on the quality of life of patients with breast cancer.